Impact of a selected Debaryomyces hansenii strain's inoculation on the quality of Sardinian fermented sausages. (July 2019) - Murgia, Marco Ambrogio; Marongiu, Antonella; Aponte, Maria; Blaiotta, Giuseppe; Deiana, Pietrino; Mangia, Nicoletta Pasqualina
Abstract: Dominant yeast species in Salsiccia Sarda, a traditional fermented sausage produced in Sardinia (Italy), were evaluated through the monitoring three typical production processes. Six different species were identified by molecular techniques, but Debaryomyces ( D .) hansenii proved to be dominant. A D. hansenii strain was selected according to its technological features and used in three experimental sausage productions at farm scale with the aim to evaluate its antifungal effect. In all cases, two batches were inoculated with a previously selected autochthonous starter cultures ( Lactobacillus plantarum and Staphylococcus xylosus ), whereas two batches were left to spontaneous fermentation. D. hansenii was inoculated on the sausages surface by brushing after the sausages drying, by immersion in a yeast suspension after the stuffing, or, alternatively, casings were dipped in a yeast suspension before the dough stuffing. Microbial counts in the sausages core did not appear to be affected by D. hansenii application, while outcomes obtained for casings appeared soundly diversified. Brushing on the sausages surface at the onset of fermentation proved to be the best approach to treat sausages. Yeast inoculation exerted a noteworthy anti-mould effect, independently of the mode of application and, on the other hand, did not affect the overall quality and typical features of the product. Graphical abstract: Unlabelled Image Highlights: Debaryomyces hansenii proved to be the dominant yeast species in Salsiccia Sarda. Isolated yeast cultures were characterized for features of technological interest. Strain Ca3 was selected and used in 3 experimental sausages productions at farm scale. The yeast exerted an anti-mould effect, independently by the mode of application. The yeast application did not affect the overall quality and features of the product.